Impact of reducing conditions on the stabilization of Mg0.2Co0.2Ni0.2Cu0.2Zn0.2O high-entropy oxide. Issue 20 (15th October 2022) - Lin, Yong; Biesuz, Mattia; Bortolotti, Mauro; Shen, Longyun; Wu, Jinghua; Baptiste, P.Y.; Yu, Jing; Ciucci, Francesco; Sglavo, Vincenzo M.; Hu, Chunfeng; Grasso, Salvatore
Abstract: The entropy stabilization effect has expanded the compositional diversity of inorganic compounds. Nevertheless, the correlation between processing conditions, properties, and microstructure remains poorly understood. So far, little attention has been dedicated to identifying processing strategies to facilitate (i.e., reduce processing temperature) the synthesis of multi-elements oxides. In this work, we have evaluated the impact of spark plasma sintering (SPS) on stabilizing Mg0.2 Co0.2 Ni0.2 Cu0.2 Zn0.2 O high entropy oxide (HEO). Compared to conventional sintering in air, the reducing conditions achieved in SPS allowed a ≈ 200 °C decrease in the temperature required to stabilize the HEO phase. The interpretation of such effect was guided by DSC/TGA, XRD, and XPS analyses. The results suggest a strong correlation between processing atmosphere (i.e., reducing, inert or oxidizing), interfacial resistance and volumetric capacity of the high entropy anode materials.